A Severe Case of Congenital Thrombotic Thrombocytopenia Purpura Resulting From Compound Heterozygosity Involving a Novel ADAMTS13 Pathogenic Variant. Issue 1 (January 2018) - Conboy, Erin; Partain, Paige I.; Warad, Deepti; Kluge, Michelle L.; Arndt, Carola; Chen, Dong; Rodriguez, Vilmarie
Abstract : We report a 9-year-old Chinese girl with congenital thrombotic thrombocytopenic purpura found to be a compound heterozygote for 2 pathogenic variants in the ADAMTS13 gene, including a novel variation. The girl suffered from recurrent, life-threatening episodes of thrombocytopenia and hemolysis, and laboratory testing showed ADAMST13 enzyme activity of <5%. Sequencing of the ADAMTS13 gene revealed a previously reported missense variant, c.1787C>T (p.Ala596Val), and a novel duplication defined as c.1007_1025dup19 (p.Asp343Leufs*53); the duplication is predicted to result in a premature stop codon and protein truncation. We propose that this novel variant is partly responsible for the patient's early-onset and severe phenotype.